Aspectos morfológicos e efeito de diferentes temperaturas sobre a biologia de Brachycaudus (Appelia) schwartzi (Borner, 1931) (Homoptera: Aphididae) - Foureaux, Lúcia Maria Victor Brígido (1996)
The objective of this research was to study morphological aspects and the biology of Brachycaudus (Appeiia) schwartzi (Bomer, 1931) (Homoptera: Aphididae) at temperaturas of 16, 21, 23 and 26°C, 70 ± 10% relative humidity and 14 hours photophase. This research was carried out at the Insect Biology Laboratory of the Universidade Federal de Lavras - UFLA, using B. (Appeiia) schwartzi collected on infested branches of peach trees. The first, second, third and fourth apterous instars and the fourth alatoid instar showed an average body length of 0.068 ± 0.013 ; 0.83 ± 0.019 ; 1.06 ±0.019 ; 1.27 ±0.032 and 1.29 ±0.041 mm, respectively; and an average antennal length of 0.29 ± 0.006 ; 0.37 ± 0.009 ; 0.49 ± 0.016 ; 0.59 ± 0.019 and 0.85 ± 0.038mm, respectively. Viviparous females apterous and winged showed an average body length of 1.29± 0.038 and 1.28 ± 0.035 mm; body width of 0.71 ± 0.022 and 0.53 ± 0.013 mm, and antennal length of 0.71 ± 0.032 and 1.01 ± 0.032 mm, respectively. There were four nymphal instars which duraction was significantly reduced with the increase of temperature from 16°C to 23°C. The nymphal period had an average duration of 15.30 days at 16°C, decreasing significantly to 13.10 days at 21 °C and to 7.40 days at 23°C. At 26°C there was a significant increase on the average duration of all instars and pre-reproductive period, when compared to 23°C. The temperature affected significantly the adult phase, with the pre-reproductive period ranging from 1.60days at 23°C to 2.85 days at 16°C. The reproductive period was 5.75 days at 26°C and 18.15 days at 16°C. Also the post-reproductive period ranged from an average duration of 4 days at 26°C to 13.10 days at 16°C. The temperature also affected the total capacity of larviposition resulting in an average of 32.55 nymphs/female at 16°C, with a significant decrease to 23.25 and 6.50 nymphs/female at 23°C and 26°C, respectively. The adult viviparous females of B. (Appeiia) schwartzi suffered a significant influence of temperature over its longevity, with an average duration of 34.10 days at 16°C and decreasing 11,50 days with the elevation of temperature to 26°C. There was a significant reduction in the average duration of the biological cycle: 49.40 days at 16°C; 43.70 days at 21°C; 26.80 days at 23°C and 20.55 at 26°C. The level of mortality was minor at 16°C with 27.50% for the nymphal stage period, increasing significantly at 30°C when all individuais died before reaching the adult stage. Among the biological phases of B. (Appeiia) schwartzi, the first instar was the most affected by temperature, while the fourth instar was less influenced. The lower threshold temperature for development of B. (Appeiia) schwartzi was 3.6°C for the nymphal period, 8.2°C for the adult and 7.5°C for the complete biological cycle. The thermal constants were 190.87 ;287.13 and 451.01 degree days, respectively. The temperature of 23°C was favourable for the development of the immature instars and for the shortage of the pre-reproductive period of B. (Appeiia) schwartzi.